Ilicicolin A Exerts Antitumor Effect in Castration-Resistant Prostate Cancer Via Suppressing EZH2 Signaling Pathway - Guo, Lang; Luo, Xiaowei; Yang, Ping; Zhang, Yanting; Huang, Jialuo; Wang, Hong; Guo, Yinfeng; Huang, Weifeng; Chen, Zhiqiang; Wang, Shusheng; Wang, Junjian; Lei, Jinping; et al. (Frontiers in Pharmacology, 2021)
The Polycomb protein enhancer of zeste homolog 2 (EZH2) has critical roles in prostate cancer (PCa) progression and drug-resistance, which remains an obstacle for PCa treatment. Enzalutamide (ENZ) is a second-generation androgen receptor (AR) antagonist employed for treatment of metastatic castration-resistant prostate cancer (mCRPC). A considerable proportion of tumors eventually develop resistance during treatment. Thus, agents that can overcome resistance to PCa are needed urgently. Ilicicolin A (Ili-A), an ascochlorin derivative isolated from the coral-derived fungus Acremonium sclerotigenum GXIMD 02501, shows antiproliferative activity in human PCa cells, but its mechanism of action against CRPC is not known. Herein, RNA-sequencing showed the EZH2 pathway to be involved in PCa proliferation. Ili-A at low doses reduced the protein level of EZH2, leading to transcriptional change. Interestingly, Ili-A suppressed the binding of EZH2 to promoter regions in AR/serine/threonine polo-like kinase-1/aurora kinase A. Moreover, Ili-A could enhance the anticancer activity of enzalutamide in CRPC cancer models. These data suggest that Ili-A could be used in combination with enzalutamide to treat CRPC.